Distribution and Conservation Gaps of Nautilus pompilius: A Study Based on Species Distribution Models - Xianshui Lai; Linlin Zhao; Wenhao Huang; Lusita Meilana; Tingting Li; Kaiyu Liu; Bei Wang; Bailin Cong; Shenghao Liu (Diversity)
Nautilus pompilius, a ‘living fossil’ of the oceans, is crucial to the study of biological evolution and paleontology. However, the species’ habitat has been severely impacted by global climate change. Based on this, species distribution models and conservation gap analyses were conducted under current and future climate scenarios. The results revealed that the current habitats for N. pompilius were primarily located in the coastal waters of Australia, Indonesia, and the Philippines. Under the Representative Concentration Pathway (RCP) 4.5 scenario, suitable habitat is projected to decline by 4.8% in the 2050s and 5.3% in 2100s. This loss is expected to intensify under higher emission scenarios, particularly RCP 8.5, where the reduction could reach 15.4% in the 2100s. Conservation gap analysis indicates that while nearly 30% of suitable habitats fall within marine protected areas (MPAs), many vulnerable regions remain unprotected. Future MPA establishment should strategically address these conservation gaps, particularly in coastal waters such as the Gulf of Carpentaria, the Arafura Sea, and the southern edge of the Timor Sea. This study provides critical insights into the distribution patterns and conservation needs of N. pompilius, emphasizing the urgent need for targeted conservation efforts to protect this endangered species.